The Effectiveness of Emotional Intelligence Psychoeducation on Learning Motivation, Self-Regulated Learning, and Procrastination in Students - Winei, Agnes Angi Dian; Wahyuningrum, Paulina Maria Ekasari; Karisma, Elia (Kuras Institute, 2025)
This research aims to determine the effectiveness of psychoeducation on emotional intelligence about changes in learning motivation, self-regulated learning, and academic procrastination. Providing Emotional Intelligence psychoeducation is hoped to increase learning motivation, self-regulated learning, and reduce academic procrastination. The research method used is a quasi-experimental one-group pretest-posttest design. The participants in this study are 63 students from STIPAS Tahasak Danum Pambelum, Palangkaraya Diocese. Participants were given an intervention in the form of emotional intelligence psychoeducation. The evaluation of the intervention used the Kirkpatrick criteria levels, namely the reaction level measured using a reaction test, the knowledge level measured with an emotional intelligence knowledge test, and the behavior level with a learning motivation scale, self-regulation scale, and procrastination scale. The results of the data analysis using the Wilcoxon Signed Ranks Test show a significant difference between before and after the psychoeducation was provided, with a learning motivation value of z = -5.848 with p = 0.00 (p<0.05), self-regulated learning value of z = -5.773 with p = 0.00 (p<0.05), and procrastination value of z = -5.440 with p = 0.00 (p<0.05). Psychoeducation on emotional intelligence is effective in increasing learning motivation, self-regulated learning, and reducing procrastination.